2017
DOI: 10.1111/jop.12555
|View full text |Cite
|
Sign up to set email alerts
|

Current update on the diagnosis and management of head and neck soft tissue sarcomas

Abstract: Head and neck soft tissue sarcomas are a group of rare heterogeneous tumours arising from embryonic mesoderm. They comprise <1% of all head and neck malignancies and 5-15% of all sarcomas with most head and neck sarcomas arising from soft tissues. Although rare, they are associated with both high recurrence and mortality rates. We review the current management of head and neck soft tissue sarcomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 53 publications
0
23
0
Order By: Relevance
“…Previous studies that included a larger cohort of 12,755 patients mentioned that further data accumulation for predictors of HNS due to rare tumors and various histological subtypes is needed [1][2][3]. Indeed, Ketabachi et al had reported that the surgical margin was a survival predictor for 25 patients with HNS [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies that included a larger cohort of 12,755 patients mentioned that further data accumulation for predictors of HNS due to rare tumors and various histological subtypes is needed [1][2][3]. Indeed, Ketabachi et al had reported that the surgical margin was a survival predictor for 25 patients with HNS [7].…”
Section: Discussionmentioning
confidence: 99%
“…Head and neck sarcoma (HNS) is a rare malignancy, with more than 50 pathological subtypes, accounting for approximately 1% of all head and neck malignancies [1,2]. Surgery is the main treatment for patients who are newly diagnosed with HNS, while the e cacy of chemotherapy or radiotherapy remains debatable for all pathological subtypes of HNS [1][2][3]. The predictors for survival outcomes of HNS, such as overall survival, have been investigated by several previous studies [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Malignant peripheral nerve sheath tumors are usually large lesions that may sometimes cause a fusiform expansion of the nerve from which they arise . Depending upon the stroma and cellularity, the tumors can be fibrous, gelatinous, or fleshy in consistency.…”
Section: Discussionmentioning
confidence: 99%
“…Adds to the failure in the treatment of this case the difficulty of monitoring the vital structures involved by the tumor mass as well as the inability to remove it in its entirety surgically, which could have increased the chances of survival for the patient 18 .…”
Section: Discussionmentioning
confidence: 99%